Integration of Financial Literacy and Ethical Values in Controlling Impulsive Buying In Generation Z on Social Media - Perdana, Baratadewa Sakti; Tamamudin; Hendri Hermawan Adinugraha (El-Barka, 2024)
This study explores the role of financial literacy and ethical values in controlling impulsive buying behavior among Generation Z, especially in the context of digital platforms. This study uses a qualitative method with Thematic Analysis to examine how these two factors affect self-control in financial decision-making. Data were collected through interviews with Generation Z respondents, which showed that strong ethical values, instilled through religious teachings and cultural culture built into the family, significantly increased self-control, even when financial literacy was limited. These findings suggest that when ethical values are combined with good financial literacy, self-control becomes increasingly strong, allowing individuals to avoid impulsive buying and make more informed financial decisions. The study also recommends the application of Imam Shafi'i's principles in prioritizing the most important and urgent needs, which translates into the